(untitled) (Chest & Heart Journal, 2023)
Background: Coronavirus disease 2019 (COVID-19) is a potentially fatal disease with multisystem involvement. Electrolyte abnormalities are not uncommon in coronavirus disease 2019 (COVID-19). Several studies have suggested that various electrolyte imbalances seem to have an impact on disease prognosis. Objective: The primary objective of the present study was to evaluate the pattern of electrolyte abnormalities in hospitalized COVID-19 patients. Methods: This retrospective study was conducted in the Department of Respiratory Medicine, National Institute of Diseases of the Chest & Hospital, Mohakhali, Dhaka, between January 2021 and June 2021. A total of 51 patients with COVID-19 were included in the study. Baseline levels of sodium, potassium, calcium and chloride were assessed and the effects of abnormalities in these electrolytes were evaluated. Patients demographic profile, clinical features, admission electrolyte report were documented in case record forms. Collected data were compiled and appropriate analyses were done by using computer based software. Chi-squre test was used to analyse the categorical variaties. A p-value <0.05 was considered significant. Results: In this study, total 51 hospitalized COVID-19 patients were included in the study. Majority (41.2%) patients belonged to age group 61 to 80 years with mean age 56.3±17.7 years. Two third (66.7%) patients were male with male to female ratio 2:1. Majority (31.4%) of the patients had hypertension followed by diabetes mellitus 29.4%, 23.5% had IHD, 15.7% had COPD and 35.3% were smoker. Most commonly electrolyte abnormality was hyponatraemia (56.9%) followed by hypokalemia (41.2%). Hyponatraemia was significantly higher in severe COVID-19 patient group. Conclusion: In this study, we found that, Hyponatraemia was the most predominant electrolyte abnormality. Hyponatraemia is a sign of unfavourable prognosis in COVID-19 and baseline electrolyte assessment, even after hospitalization, would be beneficial to assess the risk for severe COVID-19. Chest Heart J. 2021; 45(2) : 86-92